The 5′ and 3′ Untranslated Regions of the Japanese Encephalitis Virus (JEV): Molecular Genetics and Higher Order Structures - Liu, Hong; Zhang, Jun; Niu, Yuzhen; Liang, Guodong (Frontiers in Microbiology, 2021)
The UTRs of viral genome are important for viral replication and immune modulation. JEV is the most significant cause of epidemic encephalitis worldwide. However, little is known regarding the characterization of the JEV UTRs.Here, systematic analyses of the UTRs of JEVs isolated from a variety of hosts worldwide spanning about 80 years were made.All the important cis-acting elements and structures were compared with other mosquito-borne flaviviruses (WNV, YFV, ZIKV, DENV) and annotated in detail in the UTRs of different JEV genotypes. Our findings identified the JEV-specific structure and the sequence motif with unique JEV feature. (i) The 3' dbsHP was identified as a small hairpin located in the DB region in the 3' UTR of JEV, with the structure highly conserved among the JEV genotypes. (ii) The spacer sequence UARs of JEV consist of four discrete spacer sequences, whereas the UARs of other mosquito-borne flaviviruses are continuous sequences. In addition, repetitive elements have been discovered in the UTRs of mosquito-borne flaviviruses. The lengths, locations, and numbers of the repetitive elements of JEV also differed from other flaviviruses (WNV, YFV, ZIKV, DENV). A 300 nt-length region located at the beginning of the 3' UTR exhibited significant genotypic specificity. This study lays the basis for future research on the relationships between the JEV specific structures and elements in the UTRs, and their important biological function.